Du placard à l’institution : l’histoire des Archives gaies du Québec (AGQ) - Prince, Jacques (Archivaria, 2010)
Following the 25th anniversary of the Archives gaies du Québec (AGQ), the author chronicles the various steps in the development of the institution over the years. Its most important acquisitions are mentioned, as are activities relating to the acquisition and processing of collections, their preservation, and especially the diffusion of materials related to the mission of the AGQ. Questions relating to the management of an institution that relies on self-financing and volunteer-work are also addressed. RÉSUMÉ Suite au 25e anniversaire des Archives gaies du Québec, l’auteur relate les diverses étapes du développement de l’organisme, au fil des années écoulées. Les plus importantes acquisitions sont mentionnées, tout comme les activités relatives à l’acquisition et au traitement des collections, à leur conservation et surtout à la diffusion des contenus liés à la mission des AGQ. Les questions relatives à la gestion d’un organisme, dans un contexte d’autofinancement et de bénévolat, sont aussi abordées.